2018
DOI: 10.2196/10017
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Blended Care Self-Management Program for Caregivers of People With Early-Stage Dementia (Partner in Balance): Randomized Controlled Trial

Abstract: BackgroundThe benefits of electronic health support for dementia caregivers are increasingly recognized. Reaching caregivers of people with early-stage dementia could prevent high levels of burden and psychological problems in the later stages.ObjectiveThe current study evaluates the effectiveness of the blended care self-management program, Partner in Balance, compared to a control group.MethodsA single-blind randomized controlled trial with 81 family caregivers of community-dwelling people with mild dementia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(136 citation statements)
references
References 50 publications
2
132
0
2
Order By: Relevance
“…All 22 studies used the ICECAP-O alongside other measures and in all but four studies [ 15 , 51 , 53 , 56 ] this included the EQ-5D.…”
Section: Resultsmentioning
confidence: 99%
“…All 22 studies used the ICECAP-O alongside other measures and in all but four studies [ 15 , 51 , 53 , 56 ] this included the EQ-5D.…”
Section: Resultsmentioning
confidence: 99%
“…Interventions that combine face-to-face counseling with eHealth (referred to as “blended care”) are increasingly applied in the context of mental health care [ 21 ]. Moreover, promising results have been shown for using blended care in lifestyle medicine [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…This suggestion is subscribed by the Cochrane review of Dudas et al (2018) who found that there is limited evidence to support the efficacy on antidepressants for the treatment of depression in people with dementia (Dudas et al, 2018). Self-management programs which have already shown effectiveness in caregivers of people with late-onset, early-stage dementia, might also help to support caregivers of people with young-onset dementia in the management of neuropsychiatric symptoms (Boots, de Vugt, Kempen, & Verhey, 2018).…”
Section: Discussionmentioning
confidence: 99%